Pengenalan Potensi Seledri Untuk Membantu Mengatasi Penyakit Hipertensi di RT02/RW02, Kelurahan Semper Barat - Yelfi Anwar; Gabriela, Jean; Berliano Karvenio; Feby Bethariya O; Epifani Januar P (Jurnal Mitra Pengabdian Farmasi, 2023)
Webinar events are one way to educate people. The method for determining "Celery's Potential to Treat Cardiovascular Disease, Especially High Blood Pressure" has been implemented using a public Zoom meeting with participation target RT 02, rw. 02, West Semper Urban Village. The activity lasted two hours and included a pre-and post-test with five questions each. A total of 18 participants have shown significant gains in comprehension, with post-test scores averaging 89.98% compared to a pre-test average of 61.12%. Accordingly, the webinar can educate the public.